THE ROLE OF SERVANT LEADERSHIP, EMPOWERMENT, SELF-EFFICACY, MOTIVATION, AND QUALITY CULTURE IN TEACHER COMMITMENT - Suharyanto; Sri Setyaningsih; Soewarto Hardhienata (Program Studi Manajemen Pendidikan Islam, 2026)
This study aims to examine the direct and indirect effects of servant leadership, empowerment, self efficacy, work motivation, and quality culture on the organizational commitment of teachers in Center of Excellence Vocational High Schools (SMK Pusat Keunggulan), and to identify improvement strategies using SITOREM analysis. A quantitative survey was conducted on 119 teachers from 18 private Center of Excellence Vocational High Schools in Bogor Regency, selected through proportional random sampling. Instruments were adapted from standardized scales. Data were analyzed using PLS-SEM and SITOREM. The measurement model met convergent validity, discriminant validity and reliability . The R2 for organizational commitment was 0.685, indicating that 68.5% of its variance was explained by the five predictors. Work motivation had the strongest direct effect, followed by quality culture. All direct and mediating effects were significant. SITOREM identified five priority indicators for improvement sharing leadership, participation in decision making, member engagement, classroom management, achievement motivation and five outstanding indicators to be maintained. Enhancing teachers organizational commitment is most effectively achieved by strengthening work motivation and quality culture. Operational recommendations based on the priority indicators are provided for school principals and education authorities. Future research should employ longitudinal designs